The interplay between fatherhood and male identity in family life among the Ovawambo of Namibia : a pastoral hermeneutical approach - Haufiku, Johannes (Stellenbosch : Stellenbosch University, 2013)
Thesis (MTh)--Stellenbosch University, 2013.